2023
DOI: 10.1177/09731296231203809
|View full text |Cite
|
Sign up to set email alerts
|

Bee Pollen and Doxorubicin by Synergistic Effects Inhibit the Proliferation of Breast Tumors in 4T1 Tumor-bearing BALB/c Mice: A Biochemical, Immunohistochemical,and Molecular Approach

Jinwen Li

Abstract: Objectives This study investigated the effects of BP and doxorubicin (DOX) on 4T1 tumor cells in a mouse model. Materials and Methods After inducing breast tumors, 70 4T1-tumor-bearing BALB/c mice were divided into seven groups ( n = 10/group). The groups were treated with DOX and BP for 35 days. On the 36th day, blood was taken from the heart, and serum was separated to measure levels of cytokines, estrogen, progesterone, testosterone, and nitric oxide. Antioxidant enzyme activities, as well as tissue ferric-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In addition, it was noted that both BP and DOX work synergistically and upregulate the expression of apoptotic genes and proteins and eventually decrease the volume of tumor cells while decreasing the level of nitric oxide and estrogen and downregulating the level of pro-inflammatory cytokines in mice models with induced 4 T1 breast tumors. BP isoflavones have been used as anticancer agent against breast cancer cells such as triple-negative breast cancer (TNBC) and restrain the activity of endogenous estrogen ( 177 ). Research has shown that isoflavones and flavonoids of BP restrain the cell cycle at G1 and or G2/M stages and upregulate the expression of pro-apoptotic genes and dysfunction of the capability of enzymes associated with the growth and development of tumor cells while hindering the activity of intermediates such as fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF) and also inhibiting the production of ROS ( 177 , 178 ).…”
Section: Apitherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was noted that both BP and DOX work synergistically and upregulate the expression of apoptotic genes and proteins and eventually decrease the volume of tumor cells while decreasing the level of nitric oxide and estrogen and downregulating the level of pro-inflammatory cytokines in mice models with induced 4 T1 breast tumors. BP isoflavones have been used as anticancer agent against breast cancer cells such as triple-negative breast cancer (TNBC) and restrain the activity of endogenous estrogen ( 177 ). Research has shown that isoflavones and flavonoids of BP restrain the cell cycle at G1 and or G2/M stages and upregulate the expression of pro-apoptotic genes and dysfunction of the capability of enzymes associated with the growth and development of tumor cells while hindering the activity of intermediates such as fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF) and also inhibiting the production of ROS ( 177 , 178 ).…”
Section: Apitherapymentioning
confidence: 99%
“…BP isoflavones have been used as anticancer agent against breast cancer cells such as triple-negative breast cancer (TNBC) and restrain the activity of endogenous estrogen ( 177 ). Research has shown that isoflavones and flavonoids of BP restrain the cell cycle at G1 and or G2/M stages and upregulate the expression of pro-apoptotic genes and dysfunction of the capability of enzymes associated with the growth and development of tumor cells while hindering the activity of intermediates such as fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF) and also inhibiting the production of ROS ( 177 , 178 ). Wang et al concluded that BP polysaccharides (extracted from Rosa rugosa ) exhibited anticancer activity in vitro against HCT116 (human colon carcinoma) and HT-29 (colon cancer) cells in a dose-dependent way ( 179 , 180 ).…”
Section: Apitherapymentioning
confidence: 99%